Unveiling the Metabolic Changes on Muscle Cell Metabolism Underlying p-Phenylenediamine Toxicity - Marín de Mas, Igor; Marín, Silvia; Pachón, Gisela; Rodríguez-Prados, Juan C.; Vizán, Pedro; Centelles, Josep J.; Tauler, Romà; Azqueta, Amaya; Selivanov, Vitaly; López de Ceraín, Adela; Cascante, Marta (Frontiers in Molecular Biosciences, 2017)
Rhabdomyolysis is a disorder characterized by acute damage of the sarcolemma of the skeletal muscle leading to release of potentially toxic muscle cell components into the circulation, most notably creatine phosphokinase (CK) and myoglobulin, and is frequently accompanied by myoglobinuria. In the present work, we evaluated the toxicity of p-phenylenediamine (PPD), a main component of hair dyes which is reported to induce rhabdomyolysis. We studied the metabolic effect of this compound in vivo with Wistar rats and in vitro with C2C12 muscle cells. To this aim we have combined multi-omic experimental measurements with computational approaches using model-driven methods. The integrative study presented here has unveiled the metabolic disorders associated to PPD exposure that may underlay the aberrant metabolism observed in rhabdomyolys disease. Animals treated with lower doses of PPD (10mg/kg and 20mg/kg) showed depressed activity and myoglobinuria after 10 hours of treatment. We measured the serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK) in rats after 24, 48 and 72 hours of PPD exposure. At all times, treatment with PPD at higher doses (40 mg/kg and 60 mg/kg) showed an increase of AST and ALT, and also an increase of lactate dehydrogenase (LDH ) and CK after 24 hours. Blood packed cell volume and hemoglobin levels, as well as organs weight at 48 and 72 hours, were also measured. No significant differences were observed in these parameters under any condition. PPD induce cell cycle arrest in S phase and apoptosis (40% or early apoptotic cells) on mus musculus mouse C2C12 cells after 24h of treatment. Incubation of mus musculus mouse C2C12 cells with [1,2-13C2]-glucose during 24 h, subsequent quantification of 13C isotopologues distribution in key metabolites of glucose metabolic network and a computational fluxomic analysis using in-house developed software (Isodyn) showed that PPD is inhibiting glycolysis, non-oxidative pentose phosphate pathway, glycogen turnover and ATPAse reaction leading to a reduction in ATP synthesis. These findings unveil the glucose metabolism collapse, which is consistent with a decrease in cell viability observed in PPD-treated C2C12 cells and with the myoglubinuria and other effects observed in Wistar Rats treated.